Застосування теорії R-функцій для дослідження нелінійних коливань функціонально градієнтних пологих оболонок з урахуванням температурного середовища - Курпа, Лідія Василівна; Шматко, Тетяна Валентинівна (Інститут прикладних проблем механіки і математики імені Я. С. Підстригача, 2018)
Geometrically nonlinear vibrations of FGM shallow shells of an arbitrary plan-form subjected to thermal environment are investigated with the use of R-functions theory and variational methods. Nonlinear first-order shear deformation of shallow shells is employed. Material properties are assumed to be temperature dependent and varying along the thickness direction according to Voigt’s law. The effect of the temperature rise, shell geometry, and constituent volume fraction index is examined. A comparison of the obtained results with the available ones is carried out for rectangular plates and shallow shells.
Application of the R-functions theory for the investigation of nonlinear vibrations of functionally gradient shallow shells in thermal environmen
Keywords: бар'єр термічний; підхід чисельно-аналітичний; методи варіаційні; теорія Тимошенка